1972
DOI: 10.1021/ja00770a052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and some pharmacological properties of tocinoic acid and deaminotocinoic acid

Abstract: Tocinoic acid, the 20-membered cyclic disulfide ring of cysteinyltyrosylisoleucylglutaminylasparaginylcysteine, which possesses the tocin ring of oxytocin, was synthesized by the stepwise p-nitrophenyl ester method. All protecting groups of the protected intermediate Z-Cys(Bzl)-Tyr-Ile-Gln-Asn-Cys(Bzl)-ONB were removed on addition of this peptide to Na in NH3. The reduced peptide was converted to purified tocinoic acid by oxidation, followed by partition chromatography and gel filtration. Deaminotocinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Prolyl-leucyl-glycinamide (2 mg) was added to the solution of deaminotocinoic acid (5,19) (1.2mg) dissolved in dimethylformamide (20pL). After the addition of diphenyl phosphoryl azide (2pL) and diisopropylethylamine (2 pL) the mixture was shaken at room temperature.…”
Section: Deamino-oxytocinmentioning
confidence: 99%
“…Prolyl-leucyl-glycinamide (2 mg) was added to the solution of deaminotocinoic acid (5,19) (1.2mg) dissolved in dimethylformamide (20pL). After the addition of diphenyl phosphoryl azide (2pL) and diisopropylethylamine (2 pL) the mixture was shaken at room temperature.…”
Section: Deamino-oxytocinmentioning
confidence: 99%
“…We have found (7) that this syn,thetic crystalline tripeptide failed to inhibit the in vitro release of MSH from either rat or frog pituitaries, whereas hypothalamic extracts of .these species were effective inhibitors of MSH release. However, we have found that tocinoic acid (8) L-CyS-L-Tyr-L-Ile-L-Gln-L-Asn-L-Cys-OH the ring of oxytocin (9), is a potent inhibitor of MSH release from the rat pars intermedia, and we have proposed that it (or a closely related structure) may be a more likely candidate as the natural MRIF in vertebrates. We now provide additional data on the MRIFlike activity of various ring compounds related to the neurohypophysial hor- The amount of MSH released into the incubation medium from isolated pituitaries or pars intermedia is determined (10) by photoreflectance methods described originally for the frog skin bioassay for MSH (11).…”
mentioning
confidence: 99%